Grammar of Spanish legal text: why is it difficult to understand the court judgements - Olga Chibisova (Ибероамериканские тетради)
Texts of court judgements are especially difficult to understand by students of Spanish for specific purposes, not only because of legal terms, but also owing to their syntactic complexity. This study is dedicated to the main syntactic phenomena proper of the text of Spanish court judgements.